Credit cycles revisited - Jörg Urban (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2023)
Credit and business cycles play an important role in economic research, especially for central banks and supervisors. We reexamine a dynamic model proposed by Kiyotaki and Moore (1997) of an economy with an endogenous credit limit. They claim that a small temporary shock generates large and persistent deviations from the steady state due to a positive feedback loop and the endogenous credit constraint. We mathematically show that contrary to common belief the model does not show amplification and persistence is visible only for a few parameter settings. Kiyotaki and Moore have linearized the model in deviations of landholdings and found that these deviations from the equilibrium are large. This is mathematically inconsistent, because any higher order term would then be more important, rendering any finite-order Taylor expansion invalid. Further, we show that spillover effects in an economy with two distinct sectors are small. The strong amplification present in the original results, which supposedly is due to the large inter-temporal or dynamic multiplier effect, is spurious. The dynamic multiplier effect is of similar size than the static effect and in all cases numerically small.
Keywords: E32; E37; E51; E52; 330; Amplification; credit constraints; credit cycles; dynamic economies; Taylor expansion